Citrullination and PAD Enzyme Biology in Type 1 Diabetes – Regulators of Inflammation, Autoimmunity, and Pathology - Yang, Mei-Ling; Sodré, Fernanda M. C.; Mamula, Mark J.; Overbergh, Lut (Frontiers in Immunology, 2021)
The generation of post-translational modifications (PTMs) in human proteins is a physiological process leading to structural and immunologic variety in proteins, with potentially altered biological functions. PTMs often arise through normal responses to cellular stress, including general oxidative changes in the tissue microenvironment and intracellular stress to the endoplasmic reticulum or immune-mediated inflammatory stresses. Many studies have now illustrated the presence of ‘neoepitopes’ consisting of PTM self-proteins that induce robust autoimmune responses. These pathways of inflammatory neoepitope generation are commonly observed in many autoimmune diseases including systemic lupus erythematosus, rheumatoid arthritis, multiple sclerosis, and type 1 diabetes (T1D), among others. This review will focus on one specific PTM to self-proteins known as citrullination. Citrullination is mediated by calcium-dependent peptidylarginine deiminase (PAD) enzymes, which catalyze deimination, the conversion of arginine into the non-classical amino acid citrulline. PADs and citrullinated peptides have been associated with different autoimmune diseases, notably with a prominent role in the diagnosis and pathology of rheumatoid arthritis. More recently, an important role for PADs and citrullinated self-proteins has emerged in T1D. In this review we will provide a comprehensive overview on the pathogenic role for PADs and citrullination in inflammation and autoimmunity, with specific focus on evidence for their role in T1D. The general role of PADs in epigenetic and transcriptional processes, as well as their crucial role in histone citrullination, neutrophil biology and neutrophil extracellular trap (NET) formation will be discussed. The latter is important in view of increasing evidence for a role of neutrophils and NETosis in the pathogenesis of T1D. Further, we will discuss the underlying processes leading to citrullination, the genetic susceptibility factors for increased recognition of citrullinated epitopes by T1D HLA-susceptibility types and provide an overview of reported autoreactive responses against citrullinated epitopes, both of T cells and autoantibodies in T1D patients. Finally, we will discuss recent observations obtained in NOD mice, pointing to prevention of diabetes development through PAD inhibition, and the potential role of PAD inhibitors as novel therapeutic strategy in autoimmunity and in T1D in particular.